Botany teaching in Portugal and Brazil: analysis of school textbooks and their application in elementary school classes (2001- 2010) - Guimarães, Fernando (2009)
We have privileged the study of Botany contents in our research. Such contents derive from reorganizational approaches within the teaching of Natural Sciences at the elementary level in Portugal and Brazil. Along with the development of scientific knowledge on biological classifications and attempts to solve existing weaknesses in both countries, various governments introduced, throughout the last century, new programmatic Botany contents within the teaching of Natural Sciences at the elementary school. Thus, the teaching of Botany becomes more complex with the emergence of new realities, as well as curricular and didactic changes that emphasize such dimensional metamorphoses, which can be seen within classroom contexts and during the teaching-learning process. We aim to study such complex dimensions within the teaching of Botany, which is placed into a knowledge area undergoing a re-organizational approach where historical and educational circumstances mark Portuguese and Brazilian realities. This knowledge area faces important changes and new challenges resulting from significant environmental and political modifications, new practises and programmatic speeches that have been heard throughout various national and international debates. Such scientific approach on Natural Sciences favours the questioning and conceptual role played by Botany, and should clearly take into consideration the existing approaches in education and science teaching. The start point of the current study is the relevance of the teaching of Botany within the curricular and didactic structure and the importance texts have in it. Such texts come from outside the classroom and may be seen as regulating tools for the teaching practise by configuring reference universes – school textbooks and programmatic texts are examples. These texts are analysed in their specificity, articulation with the scientific speech, and relationship with the pedagogical transmission. An articulated, diachronic analysis shall be used for such aspects, i.e. with the use of an evolutionary and historical approach. The methodological approaches taken in our investigation will be both qualitative and quantitative. So that objectives are met, the overall strategy consists of the analysis of samples of various school textbooks, which will be chosen according to their application and use frequencies throughout the Portuguese territory, and within the Sao Paulo state, Brazil. Document, content and cluster analyses will be used to do so. We also aim to reach through several levels, as follows: i) Academic level, at which multiple mechanisms are allowed, i.e. deeper analyses of the educational processes to be studied, investigation team build-up and investigation unit selection; ii) Social level, at which results will be shared with the educational community directly involved with the study object; and, iii) Educational level, at which new dynamic procedures will be introduced in the teaching-learning process regarding Botany, with the production of elements that enhance its comprehension and, perhaps, its transformation. The final phase of the current project aims to build a virtual environment, with a specific website, through which researchers, teachers, scholars and other educational actors from Portugal and Brazil may share the obtained results and keep a dynamic and open tool to discuss issues related to the teaching of Botany.